Spectrofluorometric Analysis of New-Generation Antidepressant Drugs in Pharmaceutical Formulations, Human Urine, and Plasma Samples. Issue 2 (28th May 2012) - Das Das, Ruchita S. Ruchita S.; Agrawal Agrawal, Y. K. Y. K.
Abstract : Spectrofluorometric analysis for the quantification of new-generation antidepressant drugs belong to the class of selective serotonin reuptake inhibitors and selective norepinephrine reuptake inhibitors is described. Five different drugs, sertraline, paroxetine, citalopram, venlafaxine, and fluoxetine, were analysed for spectrofluorometric detection in pharmaceutical formulations and urine and plasma samples. The calibration curves were found linear between fluorescence intensity and drugs concentration in the range of 5–500 ng/μ L with coefficients of determination above 0.9985 for all the analytes. The method recoveries were higher than 85% in all the three matrices. The intra- and interday variation coefficients were observed less than 8% and 13%, respectively. The limits of detection (LOD) and limit of quantification (LOQ) were found in the range of 0.016–0.084 ng/μ L and 0.090–0.285 ng/μ L, respectively. Additionally, the results were compared statistically for each analyte in all the three matrices and were found equivalent, which signifies the absence of matrix effect. Thus, the method will be applied successfully to the determination of the cited drugs in pure or dosage forms as well as in biological fluids with good accuracy and precision.